Institute of Expedited Pre-Trial Investigation: National and International Experience - SMAILOV, Omerbay; ABDELDINOV, Serik (Journal of Advanced Research in Law and Economics, 2020)
The article examines the institute of expedited pre-trial investigation in the criminal proceedings of Kazakhstan. This institute has been recently introduced into the Kazakh criminal procedure legislation, although it has been known and applied in the international practice for many years. The introduction of this institute into criminal proceedings was due to the legislator's striving to minimize the time needed to investigate some criminal cases, achieve procedural economy and reduce procedural costs. However, not all scholars and law enforcers support such optimization of criminal proceedings, some of them criticize this institute and believe that it gravely violates the individual's rights. In addition, the use of this procedure for investigating criminal cases raises many questions, which the existing regulation cannot answer. Thus, it is relevant to analyze expedited pre-trial investigation. The article aims to study the expedited pre-trial investigation of criminal cases in Kazakhstan and the international application of this institute, as well as to draw conclusions and offer suggestions for improving the existing regulatory and procedural practice. The authors of the article consider the procedural peculiarities of expedited investigation and the subsequent resolutions made by authorized persons, as well as note advantages and disadvantages of the institute under study and gaps in the existing legal regulation. The article examines the differentiation of preliminary investigation forms as a global trend and demonstrates the continuity of international experience while introducing expedited investigation into the criminal process. The authors suggest several improvements to the current criminal procedure legislation of Kazakhstan, which decreases legal uncertainty during the application of expedited pre-trial investigation